Kandungan Fitokimia dan Aktivitas Farmakologi Tanaman Mangrove Jeruju (Acanthus ilicifolius): Narrative Review - Audrea Arnetta Deandra; Diva Atfal Prayoga; Elmiawati Latifah; Arief Kusuma Wardani; Puspita Septie Dianita; Prasojo Pribadi; Heny Setyowati Esti Rahayu; Kartika Wijayanti (Universitas Muhammadiyah Klaten, 2024)
Mangroves are woody plants that thrive in wet, muddy, and brackish water habitats found in tropical and subtropical regions. Mangroves are commonly found in Indonesia. One type of mangrove plant is Acanthus ilicifolius L., which can be utilized for medicinal purposes due to its phytochemical content. The aim of this narrative review is to provide information and an overview of the potential phytochemical and pharmacological activities present in each part of the mangrove plant jeruju, along with the solvents and testing methods used. The method employed in this narrative review involves searching for relevant articles on the internet through databases such as Google Scholar, Springer Open, Science Direct, and PubMed. According to several studies, methanol solvent yields the best results as it extracts the most phytochemical content from the mangrove jeruju. The leaves and stems of the mangrove jeruju are the most researched parts because they are the most dominant and easiest to treat. Research findings indicate that the leaves and stems of the jeruju plant contain the highest amounts of alkaloids, tannins, terpenoids, phenols, and flavonoids, with antimicrobial activity being the most commonly found pharmacological potential.